MINAPOLITAN UNTUK MENDUKUNG KETAHANAN DAN KEAMANAN PANGAN - Bambang Pujiasmanto; Sutopo Sutopo; Istijabatul Aliyah; Mulyanto Mulyanto (Caraka Tani: Journal of Sustainable Agriculture, 2015)
The objectives of this research were to: (1) identify the potentials of fish resources in  Klaten regency which can be developed as the economic generator of the community; (2) analyze the provision of fish products to support food security and safety for the surroundng region; (3) analyze the process of managing fish to perform food safety and security; 4) analyze the supporting factors of  fish resources management in Klaten to develop the community economy; 5) analyze the constraints of managing fish resources in Klaten to develop the community economy; 6) analyze the policy and programs of the local Government of Klaten in developing the potenstials of fish resources; particularly fish cultivation; and (7) formulize an appropriate method to manage fish resources to improve the community economy and support food security and safety. This research applied descriptive approach and was qualitative in nature. Data were collected using several methods including site observation, in-depth interview, focus group discussion, document study, and super impose. Sampling technique used in this research were purposive sampling and snowball. Data were analyzed using (1) Human Resources Analysis (2) Policy Analysis (3) Interactive Analysis. Research results include: (1) method to manage fish resources to improve the community economy and support the food security and safety; 2) recommendation in the form of Memorandum of Understanding (MOU) related to the method to manage fish resources to improve the community economy and support the food security and safety; and 3) handouts concerning method to manage fish resources to improve the community economy and support the food security and safety.